A prospective study of personality and illicit drug use in Australian adults. (1st September 2020) - Allen, Mark S.; Laborde, Sylvain
Abstract: This study explored whether personality relates to past and subsequent use of illicit drugs. A near-representative sample of 12, 525 Australian adults (5772 men; 6743 women) completed self-report measures of personality at baseline and returned to complete measures of personality and illicit drug use four years later. After controlling for sociodemographic factors, higher levels of neuroticism, extraversion and openness, and lower levels of agreeableness and conscientiousness, were associated with a greater likelihood of subsequent illicit drug use, as well as a greater likelihood of having ever used an illicit drug. Increases in openness and decreases in conscientiousness over four years were also associated with a greater likelihood of recent illicit drug use. These findings were relatively consistent for cannabis, methamphetamine, cocaine, ecstasy, and hallucinogens. There were no sex moderation effects, but the association between openness and likelihood of having ever used an illicit drug was stronger among older adults. Personality traits were unrelated to age of first use of an illicit substance. Small–medium effect sizes were observed for personality dimensions combined, and small effect sizes were observed for individual effects. Overall, findings indicated that openness and conscientiousness were most strongly related to past and subsequent illicit drug use.